PEMIKIRAN EKONOMI IBN KHALDUN - Lubis, Sadam Zulkhairi; Mukti, Mhd.Farhan (CV. Pusdikra Mitra Jaya, 2025)
The most prominent Muslim intellectual and his most thought about economics is Ibn Khaldun. (1332-1406). Ibn Khaldun had many thoughts in various fields, such as economics, politics and culture. One of Ibn Khaldun's thoughts that is very prominent and very important to discuss is his thoughts on economics. The importance of discussing Ibn Khaldun's thoughts on economics because his thoughts have great significance for the development of Islamic economics going forward. In addition, this paper also wants to show that Ibn Khaldun was the father and economist who preceded Adam Smith, Ricardo and European economists.